Potential benefits of adaptive control strategies are outweighed by costs of infrequent, but dramatically larger disease outbreaks - Samuel M. Smith; Colleen T. Webb; Stefan Sellman; Tom Lindström; Lindsay M. Beck-Johnson (Royal Society Open Science)
Understanding underlying transmission dynamics is necessary to effectively control an infectious disease outbreak. In the likely event that managers do not know where to target control resources because drivers of transmission are unknown, it may be desirable to tailor control strategies to a given outbreak by implementing control actions gradually in response to changes in the outbreak (adaptive) rather than all at once (fixed). Adaptive control strategies may also prevent over-reaction and thus causing unnecessary socioeconomic harm. However, it remains unclear whether the benefits of adaptive control strategies outweigh the potential of under-reacting and causing larger outbreaks. To weigh this trade-off, we used a validated national scale foot and mouth disease transmission model to compare how adaptive and fixed control strategies as well as various attributes of the control process affect outbreak size. We find that adaptive control strategies do not cost less for the vast majority of outbreaks, but infrequently result in much larger and more costly outbreaks owing to decision-making time and case reporting lags. This study emphasizes the cost of under-reacting to a disease outbreak and that minimizing decision-making time should be a key consideration when developing outbreak response guidelines.